Venous Thrombosis Following Diagnostic Transvenous Catheterization by Percutaneous Catheter Insertion: An Evaluation of Desmopressin as a Thromboprophylactic Agent - Nilsen, D W T; Haerem, J; Westheim, A; Skjennald, A; Grendahl, H; Godal, H C (Thrombosis and Haemostasis, 1984)
The preventive effect of desmopressin with respect to catheter induced thrombosis was studied in a randomized double-blind trial, consisting of 30 patients undergoing percutaneous transcubital right heart catheterization. Phlebography of the catheterized arm was performed after five days. The frequency of postcatheterization thrombosis was reduced by 33 per cent, from 86 per cent in the treatment group to 53 per cent in the control group (0.1 <p <0.2). This effect was restricted to minor thrombi, whereas major thrombosis could not be prevented.Patient materials such as that of the present study, may become useful in preliminary investigations of thromboprophylactic agents.
Keywords: Transvenous catheterization; Desmopressin; Fibrinolysis; Venous thrombosis